An evaluation of geochemical weathering indices in loess–paleosol studies - Buggle, Björn; Glaser, Bruno; Hambach, Ulrich; Gerasimenko, Natalia; Marković, Slobodan (Quaternary international, 2011)
Applying geochemical proxies as measure for the weathering intensity of paleosols and sediments such as loess, the Quaternary scientist is confronted with various element ratios that have been proposed in literature. This paper gives an overview on the principle of geochemical weathering indices. Different types of indices are evaluated with respect to the suitability for loess–paleosol sequences, regarding the special characteristics of this type of sediments and paleosols. Case examples in this study are key sections in Southeastern and Eastern Europe: the loess–paleosol sequences Batajnica/Stari Slankamen (Serbia), Mircea Voda (Romania) and Stary Kaydaky (Ukraine), which represent archives of the Late and Mid-Pleistocene climate change of the region. Considering element behavior during weathering or diagenesis, the Chemical Proxy of Alteration (CPA) – i.e. the molar ratio Al 2O 3/(Al 2O 3 + Na 2O) × 100 – is proposed as the most appropriate index for silicate weathering. The CPA was evaluated against commonly used weathering indices including the “Chemical Index of Alteration” (CIA), the “Chemical Index of Weathering“ (CIW), the “Plagioclase Index of Alteration“ (PIA), the Index B of Kronberg and Nesbitt, and the Ba/Sr and Rb/Sr ratio. Depth profiles of “Sr-type indices” (e.g. Ba/Sr, Rb/Sr) are likely to be influenced by the dynamics of secondary carbonate. On the other hand, common “Na-type indices” (e.g. CIA, PIA, CIW) may suffer from uncertainties in separating carbonate–Ca from silicate–Ca or from biases due to K-fixation (illitization). The CPA is insensitive against such effects. Additionally, using the CPA (as with other Na-type indices) provides the possibility to evaluate the homogeneity of the parent material regarding the relevant host minerals via the A–CN–K diagram.